A tessitura do ensaio em Theodor W. Adorno - Viana, Cynthia Maria Jorge (2015)
This PhD research, developed in the Postgraduate Program in Education, following the line of research Foundations of the Educational Processes and based in the Critical Theory of Society of the Frankfurt School, mainly in the contributions of the German philosopher Theodor W. Adorno, aimed at reflecting about the essay according to his text The Essay as Form (Der Essay als Form). This study took as an emblem the procedure of reason revealed by the essay, which, also as a procedure of reason and form of exposition, is constituted through mediations that allow to think about its epistemological potentialities as another procedure of reason. Thus, this dissertation researches such procedure in the constitutive mediations: the relations of subject and object, form and content and reason and experience. Such mediations dispense with essay and can very well be investigated by means of other objects. In the essay, they make it possible to denounce and criticize the domain of instrumental reason and the knowledge that is established as ideology. If the historical tradition of essay leads to Montaigne, with the publication, in 1580, of Essais – in which the object of the essay is the subject Montaigne, and the content of its form is the author’s own life –, with Adorno the essay is the synthesis of mediations, groping intention, stage of the intellectual experience that exposes contents that can only be exposed in this other procedure. In revealing itself through the fragment in a fragmented, unsystematic and discontinuous way, the essay is a negative praxis that makes possible the experience in the genuine contact with objects. The essay, by means of its procedure and exposition, guards the condition of possibility of the knowledge and different communication between a real subject and an object that is also real. Its form is content and its content is form and, in this sense, the essay does not give in to lighten that which obstructs experience. Definitely, the essay moves away from the line of action of the culture industry for not condoning with an accelerated and operational textual communication. It explicitly resists becoming a totalizing language. Thus, the essay is a protest against the domain of operational reason and science.